Dynamics of journalistic education in regional Kazakhstani universities: based on 2015-2018 (Herald of Journalism, 2020)
The new millennium has led to significant changes in journalism and journalism education. Of course, this affected not only journalism, but also almost all areas of the social sciences. The first reason for this is the technological boom over the past 20 years. With the transition from analog to digital, the old-fashioned practice of journalism has been disrupted. As people or consumers live in a digital world, journalism education needs to evolve and, in some cases, train professionals for the future. This can only be done as a result of the joint efforts of teachers, students and journalists. And this result is directly related to the educational programs of educational institutions. Therefore, the study of subjects in curricula, their learning objectives and learning outcomes is relevant. Many foreign and domestic scientists have conducted a number of studies in this area. Previous studies were conducted by questioning students, teachers and practicing journalists or by comparing domestic journalism education programs with foreign ones. Some studies have also been devoted to journalism and journalism education from a political science perspective. Main objectives of research are: 1) to study and determine the dynamics of the development of modular curricula of higher education institutions, i.e. 4 year study program; 2) conducting in-depth interviews with four teachers who contributed to the creation and establishment of regional journalism schools, as well as with graduates of four selected higher education institutions; 3) study of the received programs and applications for the diploma using the method of encoding objects.As a result, the following indicators can be noted: the dynamics and changes in the development of journalism education programs in regional universities are determined; there is reason to say that they are developing in accordance with the requirements of the time, the needs of the labor market and the domestic policy of the state; in regional universities far from central cities, there is a lack of specialists in the teaching of professional disciplines and, accordingly, the uniformity of the content of other subjects.This study can be used by faculties and departments that teach journalism in developing their own programs, in identifying gaps between practical journalism and theoretical journalism, as well as in pro-moting basic research in journalism education.
Keywords: Journalism, journalism education, regional journalism, problems of educating journalists.